1996
DOI: 10.1007/bf03349029
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the mechanism of the mineralocorticoid action of licorice in humans

Abstract: The pathogenesis of pseudohyperaldosteronism from licorice has been evaluated in 6 male volunteers taking daily 7 g of a commercial preparation of licorice for 7 days, corresponding to an intake of 500 mg/day of glycyrrhizic acid. Pseudohyperaldosteronism was evident during the treatment (increase of body weight, suppression of plasma renin activity and plasma aldosterone, reduction of serum potassium). The ratio (tetrahydrocortisol + allo tetrahydrocortisol)/tetrahydrocortisone in urine increased in 5 cases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 20 publications
4
35
1
1
Order By: Relevance
“…11b-HSD type 1 is highly expressed in the liver and also acts as pre-receptor modulator of cortisol effects in most tissues. Reports suggest that licorice inhibits 11b-HSD type 1 (18,30), but this is not in agreement with our findings. As expected, if 11b-HSD type 1 was indeed inhibited, reduced hepatic first pass activation of CA would decrease cortisol C max and increase T max .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…11b-HSD type 1 is highly expressed in the liver and also acts as pre-receptor modulator of cortisol effects in most tissues. Reports suggest that licorice inhibits 11b-HSD type 1 (18,30), but this is not in agreement with our findings. As expected, if 11b-HSD type 1 was indeed inhibited, reduced hepatic first pass activation of CA would decrease cortisol C max and increase T max .…”
Section: Discussioncontrasting
confidence: 99%
“…It is possible that inhibition of 11b-HSD type 1 requires larger concentration of glycyrrhetinic acid than 11b-HSD type 2. In the report by Armanini et al (30), 500 mg glycyrrhetinic acid/day was administered for 3 days, which is more than three times the dose used in our study.…”
Section: Discussionmentioning
confidence: 98%
“…The endocrine effects of licorice haved been observed, and it has been demonstrated that licorice can produce pseudoaldosteronism by inactivating 11b-hydroxysteroid dehydrogenase (11b-HSD) and binding to mineralocorticoid receptors, leading to vasoconstriction and hypertension [4,5,7,11,12,15,43].…”
Section: Introductionmentioning
confidence: 99%
“…to its plasma concentration being more than 5000 fold the concentration of aldosterone [Armanini et al 1996]. Patients with postural hypotension caused by diabetic autonomic neuropathy have also shown improvement with licorice ingestion [Basso et al 1994].…”
Section: Health Benefits Of Licoricementioning
confidence: 99%